KEBIJAKAN PEMERINTAH INDONESIA DALAM MENGATASI EKSPLOITASI SEKSUAL KOMERSIAL ANAK (Studi Kasus : Eksploitasi Seksual Komersial Anak (ESKA) Indonesia di Singapura Tahun 2002-2007) - Hanif Asnofi; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research deals with the commercial sexual exploitation of childrenwhich occurred in Indonesia between 2002-2007 where it involves sexualexploitation in Singapore as the country that uses child sex Indonesia services thisresearch aims to know the policies or measures the Government on the protectionof Children in order to provide protection on commercial sexual exploitation ofchildren.The results showed that the Government's policy on the protection ofChildren has not been implemented to its full potential, it is caused by severalfactors, namely: first, in terms of substance, the Government do not haveregulations governing the protection of children, especially child prostitution,both in terms of the structure still lack that special institutions provided by theGovernment for child victims of commercial sexual exploitation.In this studyrecommended several positive steps such as making special laws to protectchildren, especially child victims of CSEC, improve facilities and infrastructure(set up specifically for the rehabilitation of child victims of CSEC, NGOsspecifically dealing with child victims of CSEC, database development childvictims of CSEC) in order achieve maximum results, improving cooperationbetween the Government with relevant agencies, to disseminate laws andregulations relating to the protection of children, especially child victims of CSECKey words : Sexual Explotation, Government's policy, and Protection of children